2018
DOI: 10.1136/archdischild-2017-314637
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate changes during positive pressure ventilation after asphyxia-induced bradycardia in a porcine model of neonatal resuscitation

Abstract: In contrast to NRP recommendation, adequate PPV does not increase HR within 15 s after ventilation in piglets with asphyxia-induced bradycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…However in contrast to the NRP, Espinoza et al showed that adequate PPV does not increase HR within 15 s of ventilation in piglets with asphyxia-induced bradycardia; after 30 s of PPV only half of piglets had an increase in HR. This study challenges the current NRP statement and suggests that clinicians should not expect an increase in HR after 15 s of PPV if there is severe bradycardia [42].…”
Section: Hemodynamicscontrasting
confidence: 70%
See 1 more Smart Citation
“…However in contrast to the NRP, Espinoza et al showed that adequate PPV does not increase HR within 15 s of ventilation in piglets with asphyxia-induced bradycardia; after 30 s of PPV only half of piglets had an increase in HR. This study challenges the current NRP statement and suggests that clinicians should not expect an increase in HR after 15 s of PPV if there is severe bradycardia [42].…”
Section: Hemodynamicscontrasting
confidence: 70%
“…Espinoza et al examined the changes in HR during adequate PPV following severe bradycardia in the porcine model of hypoxia-asphyxia [42]. The Neonatal Resuscitation Program (NRP) states that if adequate PPV is given for low HR, then the infant's HR should increase within the first 15 s of PPV.…”
Section: Hemodynamicsmentioning
confidence: 99%
“…PEA is a phenomenon that occurs when cardiac output is zero but the ECG still displays an HR. PEA involves cardiac electrical activity in the absence of a detectable pulse and has been reported in adults and children, most commonly after hypoxia, severe volume loss, sepsis, tension pneumothorax or following cardiac arrest [7]. There is increasing evidence that PEA occurs in the delivery room [15].…”
Section: Pulseless Electrical Activitymentioning
confidence: 99%
“…Espinoza et al used a post-transition asphyxia-induced bradycardia term piglet model and observed an increase in HR >100 bpm in only 6/30 (20%) piglets after 30 s of adequate PPV [7]. The current NRP recommendation contrasts this observation, stating that 15 s of PPV at birth should result in an increase in HR [4].…”
Section: Introductionmentioning
confidence: 99%
“…While these data suggest that an increase in HR might be delayed despite adequate ventilation, the Neonatal Resuscitation Program textbook states that once PPV is started, an increase in HR should be observed within 15 s [47]. However, in severe bradycardic asphyxiated newborn piglets, HR increased only in 50% of piglets after 30 s of adequate PPV [48]. Saugstad et al [49] reported that the HR of asphyxiated newborn infants was mean (SD) 93 (33) and 113 (30) at 60 and 90 s after birth, respectively.…”
Section: Respiratory Supportmentioning
confidence: 99%